Drosophila exercise, an emerging model bridging the fields of exercise and aging in human - Ding, Meng; Li, Hongyu; Zheng, Lan (Frontiers in Cell and Developmental Biology, 2022)
Exercise is one of the most effective treatments for the diseases of aging. In recent years, a growing number of researchers have used Drosophila melanogaster to study the broad benefits of regular exercise in aging individuals. With the widespread use of Drosophila exercise models, we should carefully examine the differential contribution of regular exercise in the aging process to facilitate more detailed quantitative measurements and assessment of the exercise phenotype. In this paper, we review some of the resources available for Drosophila exercise models. The focus is on the impact of regular exercise or exercise adaptation in the aging process in Drosophila and highlights the great potential and current challenges faced by this model in the field of anti-aging research.